Statistical Microdata - Production of Safe Datasets, Transparent Presentation of Contents and Advanced Services for Users through Metadata Authorization System - Poljičak, Martina; Stančić, Hrvoje (2014)
In the European Statistical System (ESS) there are more and more generic information systems (ISs) being developed and implemented for production and dissemination of official statistics (OS) macrodata datasets. These generic systems are based on metadata repositories providing, in return, a whole set of additional functionalities and services for users of the systems. Microdata dissemination, being the youngest and least developed discipline in official statistics dataset dissemination, currently still lacks appropriate organization of business procedures and compatible generic tools for the purpose of integration of all the ESS’ subsystems into one central Data Service (DS) providing microdata datasets for international users and enabling preservation of microdata datasets. The authors analyze current situation regarding statistical microdata sets acquisition and preservation in digital archives (DAs), provide valuable considerations and propose recommendations to take into account when developing repositories and systems for presentation of available microdata datasets to users. Along with that, the authors introduce the way of usage of appropriate Statistical Disclosure Control (SDC) methods for production of safe microdata outputs. Finally, the authors recommend the development of a central administrative metadata repository that could be used for users’ authorization, and that could have additional services for users based on available metadata about users in the system.
ENG